Impact of Diverse Immune Evasion Mechanisms of Cancer Cells on T Cells Engaged by EpCAM/CD3-Bispecific Antibody Construct AMG 110 - Deisting, Wibke (PLoS One, 2015)
BACKGROUND: Bispecific T cell engager (BiTE(®)) are single-chain bispecific antibody constructs with dual specificity for CD3 on T cells and a surface antigen on target cells. They can elicit a polyclonal cytotoxic T cell response that is not restricted by T cell receptor (TCR) specificity, and surface expression of MHC class I/peptide antigen complexes. Using human EpCAM/CD3-bispecific BiTE(®) antibody construct AMG 110, we here assessed to what extent surface expression of PD-L1, cytoplasmic expression of indoleamine-2,3-deoxygenase type 1, Bcl-2 and serpin PI-9, and the presence of transforming growth factor beta (TGF-β), interleukin-10 (IL-10) and adenosine in culture medium can impact redirected lysis by AMG 110-engaged T cells. METHODS: The seven factors, which are all involved in inhibiting T cell functions by cancer cells, were tested with human EpCAM-expressing Chinese hamster ovary (CHO) target cells at levels that in most cases exceeded those observed in a number of human cancer cell lines. Co-culture experiments were used to determine the impact of the evasion mechanisms on EC(50) values and amplitude of redirected lysis by AMG 110, and on BiTE(®)-induced proliferation of previously resting human peripheral T cells. FINDINGS: An inhibitory effect on redirected lysis by AMG 110-engaged T cells was seen upon overexpression of serpin PI-9, Bcl-2, TGF-βand PD-L1. An inhibitory effect on induction of T cell proliferation was only seen with CHO cells overexpressing IDO. In no case, a single evasion mechanism rendered target cells completely resistant to BiTE(®)-induced lysis, and even various combinations could not. CONCLUSIONS: Our data suggest that diverse mechanisms employed by cancer cells to fend off T cells cannot inactivate AMG 110-engaged T cells, and that inhibitory effects observed in vitro may be overcome by increased concentrations of the BiTE(®) antibody construct.